2006
DOI: 10.1002/ca.20318
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for classification of the suprascapular notch: A study on 423 dried scapulas

Abstract: The present study proposes a simple and reproducible method to classify the morphology of the suprascapular notch (SSN), on the basis of specific geometrical parameters that clearly distinguish one type from another. Four hundred twenty-three dried scapulas from the Department of Anatomy in the University of Cologne, Germany, were examined. Five types of SSN were observed: type I, without a discrete notch, 35 (8.3%); type II, a notch that was longest in its transverse diameter, 177 (41.85%); type III, a notch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
130
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(151 citation statements)
references
References 22 publications
17
130
2
2
Order By: Relevance
“…FIG-3 shows Type I-Wide depression in the superior border of the scapula Type II-Wide blunted V shape, Type IIISymmetric U shape Type IV-Very small V shape, often with a shallow groove for the suprascapular nerve Type V-Partial ossified medial portion of the suprascapular ligament Type VI-Completely ossified suprascapular ligament forming foramen. In the present study, Type III was more common which was similar to the observation of other studies, followed by type II which was similar to the findings of Rengachary et al, [6] and Natsis et al [13] . It differed from the studies of Sinkeet et al [14] and Sangam et al [17] which showed type I as most prevalent (Table 4).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…FIG-3 shows Type I-Wide depression in the superior border of the scapula Type II-Wide blunted V shape, Type IIISymmetric U shape Type IV-Very small V shape, often with a shallow groove for the suprascapular nerve Type V-Partial ossified medial portion of the suprascapular ligament Type VI-Completely ossified suprascapular ligament forming foramen. In the present study, Type III was more common which was similar to the observation of other studies, followed by type II which was similar to the findings of Rengachary et al, [6] and Natsis et al [13] . It differed from the studies of Sinkeet et al [14] and Sangam et al [17] which showed type I as most prevalent (Table 4).…”
Section: Resultssupporting
confidence: 92%
“…Therefore various studies have been done on suprascapular notch variations in different populations. Rengachary et al, [6] Ticker et al, [11], Bayramoglu et al, [12] Natsis et al, [13] Sinkeet [14] Wang [15] and Polguj [16]. Depending on the shape of suprascapular notch and the degree of ossification, Rengachary et al, [6] classified SSN into six types .…”
Section: Resultsmentioning
confidence: 99%
“…This approach is independent of the visualization of the suprascapular notch, as the notch is absent in 8% of the population. 14 In conclusion, we present a case report and the results of cadaver dissections, which suggest a reinterpretation of the ultrasound image obtained and described in the literature. By positioning the ultrasound probe in the coronal plane over the suprascapular fossa with a slight anterior tilt, the SSN can be visualized on the floor of the scapular spine between the scapular notch and the spinoglenoid notch.…”
Section: Discussionsupporting
confidence: 62%
“…The classification given by Natsis et al seems to be simple and includes all the anatomical variations based on the vertical and transverse diameters of the SSN. 5 The classification by Iqbal et al also provides an easy method of distinction of SSN based on its shape (U, V, and J) without involving any measurements. 4 The results of the present study show that the most common type of SSN is type II-a notch that is longest in its transverse diameter (52%) and the least common is Type V where both notch and foramen present are present (1%).…”
Section: Discussionmentioning
confidence: 99%
“…3 SSN has been classified by various workers in different populations on the basis of parameters such as vertical length of the notch, transverse diameter of the notch and shape of the notch. 4,5,6,7,8 Knowing the anatomical variations in detail is better for understanding of location and source of the entrapment syndrome.However, the literature focusing on SSN and SN IJBAR (2013) 04 (01) www.ssjournals.com…”
Section: Introductionmentioning
confidence: 99%